Programmatic Assessment in a Virtual Learning Environment: Supporting Faculty Engagement for a Successful Quality Assurance System - Kline, Amy (Frontiers in Education, 2022)
Quality P-12 student learning begins with quality educator preparation. An integral part of ensuring quality academic programs is ongoing programmatic assessment. Faculty and administrators tasked with overseeing the assessment processes in higher education institutions were faced with an added challenge during the Covid-19 pandemic when campuses across the country pivoted to virtual and hybrid learning. This transition not only meant that faculty and students were now teaching and learning in an online environment, but it also meant that assessment coordinators needed to find new ways to keep their quality assurance system operating well, while working in a pandemic, or post-pandemic reality. This chapter details how one assessment coordinator navigated the challenges and successes of supporting faculty engagement in a fully online programmatic assessment process in a college of education in a private university in the northeast.